2018
DOI: 10.3332/ecancer.2018.843
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of comorbidities in cancer patients in Lagos, South-Western Nigeria

Abstract: PurposeComorbidities have been indicated to influence cancer care and outcome, with strong associations between the presence of comorbidities and patient survival. The objective of this study is to determine the magnitude and pattern of comorbidities in Nigerian cancer populations, and demonstrate the use of comorbidity indices in predicting mortality/survival rates of cancer patients.MethodsUsing a retrospective study design, data were extracted from hospital reports of patients presenting for oncology care b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
6
12
0
Order By: Relevance
“…The similarity of these findings could be as result of the resemblance in the cosmopolitan characteristics of the participants and other psychosocial difficulties of living with cancer in the country. As noted earlier, many peculiar factors come to play from the early period of cancer inception, during treatment to recovery in Nigeria 10–15 . Moreover, biological studies revealed that immunological activities to fight off cancer cells have been implicated in the evolution of depressive disorders in the population of patients with cancers 8,9 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The similarity of these findings could be as result of the resemblance in the cosmopolitan characteristics of the participants and other psychosocial difficulties of living with cancer in the country. As noted earlier, many peculiar factors come to play from the early period of cancer inception, during treatment to recovery in Nigeria 10–15 . Moreover, biological studies revealed that immunological activities to fight off cancer cells have been implicated in the evolution of depressive disorders in the population of patients with cancers 8,9 .…”
Section: Discussionmentioning
confidence: 93%
“…During treatment, the financial burden and poor compliance with medications are possible interfering factors 12,13 . Frequently, there are associated co‐morbidities of other medical conditions such as diabetes mellitus, hypertension and peptic ulcer disease, 14 and dealing with these other conditions at the same time can be challenging to the patient and the health facilities. Moreover, people travel long distances in other to access quality cancer treatment because of few treatment centres in the country 15 .…”
Section: Introductionmentioning
confidence: 99%
“…When compared with HICs, a possible explanation for the lower prevalence of comorbid disease in our study and other studies from SSA may be the younger mean ages at presentation (53 -56 years). [27][28][29][30][31][32][33] Aside from SSA, younger mean ages (45 -67 years) have been observed in South Asia, China and Brazil. [34,35] Collectively, these findings from LMICs contrast with those from HICs, where median ages are ~10 -15 years older, and comorbidity is twice as high and adversely affects…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of conditions coexisting in adults with cancer, especially chronic conditions such as hypertension, diabetes, peptic ulcer, and other cardiovascular conditions has been described in literature [ 15 18 ]. There is, however, a paucity of information on the prevalence of coexisting conditions in children with cancer in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, a paucity of information on the prevalence of coexisting conditions in children with cancer in South Africa. Cognizance of coexisting conditions in patients with cancer is important due to their possible influence on treatment decisions—by the modification of treatment protocols—and the consequent impact on treatment outcome [ 1 , 15 , 19 21 ]. This study, therefore, aimed at identifying conditions that coexist with cancer in children and adolescents undergoing cancer chemotherapy in the South African private health sector.…”
Section: Introductionmentioning
confidence: 99%